eWOM, eReferral and gender in the virtual community - Abubakar, Mohammed Abubakar; İlkan, Mustafa; Şahin, Pınar (Emerald Insight, 2016)
Purpose – The purpose of this paper is to examine the influence of electronic referral (eReferral) marketing and electronic word-of-mouth (eWOM) on brand image and purchase intention, coupled with the moderating effect of gender in the relationship. Design/methodology/approach – Structural equation modeling was applied to examine the interplay between the proposed variables, using a random sample of 308 respondents in Cyprus. Findings – The empirical results suggest the following: eReferral does influence brand image, and the impact is significant with women only; eWOM influences brand image, and the impact is more significant with women than men; eWOM influences purchase intention, and the impact is the same for both genders; brand image influences purchase intention, and the impact is more significant with women than men. Research limitations/implications – Marketing managers can benefit from these competitive advantage tools. Brand image, awareness and sales volume can be increased by utilizing eWOM or eReferral, depending on the product and/or service functionality as well as gender. Originality/value – While there is a substantial research stream on eWOM, to the best of the authors’ knowledge no research has differentiated eReferral from eWOM. This paper provides useful insights regarding the two concepts.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Gender, Cyprus, Brand image, eReferral, eWOM, Purchase intention; Marketing strategy/methods, Marketing, Cyprus; Purchase intention, eReferral, Brand image, Gender; eWOM, Word of mouth marketing, Management, Planning, Tourism, Word of mouth advertising; Communication, Studies, Project management; Knowledge management, Customer services, MIS, Virtual communities, Credibility, Product reviews, Research